Prediction method for plastic dynamic response of hull plate subjected to ice floe impact - Wei CAI; Ling ZHU; Luze BI (Zhongguo Jianchuan Yanjiu, 2021)
ObjectivesPolar ships are often subjected to ice floe impact during navigation, particularly, hull plates may suffer permanent plastic deformation under extreme ice impact loads, affecting the safety and working performance of the ship, and greatly increasing the maintenance costs. Therefore, it is necessary to propose a method to predict the dynamic plastic response of hull structure under ice floe impact loads. MethodsThis paper analyzes the energy sharing mechanism of ice-hull interaction based on the energy analysis method and rigid-plastic theoretical method to predict the plastic dynamic response of hull plates. An analytical formula for the dynamic response of a hull plate under ice floe impact is proposed, and comparisons between the analytical and numerical results are made. ResultsThe comparisons show that the presented analytical method is reliable, this simplified theoretical analysis method can provide designers with rapid prediction regarding the maximal plastic deformation and collision force of a hull plate under ice floe impact. ConclusionsThe research has giving it great significance for engineering applications.